2010
DOI: 10.2478/s11536-009-0115-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of sevoflurane and desflurane on postoperative arrhythmia and QT dispersion

Abstract: AbstractThe aim of this study was to investigate the effect of sevoflurane and desflurane on cardiac arrhythmias in adult patients who will be anesthetized. A total of 40 patients who were in the ASA I–II group and who were to undergo elective surgery were included in the study. No pre-medication was administered to the patients. They were monitored with the Holter equipment at preoperative 24 hours, and also at postoperative 24 hours on condition that Holter monitoring will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Desflurane was associated with persistent QTc prolongation (up to 30 min) in children, 54 and a high incidence (70%) of postoperative ventricular arrhythmias in adults. 68 A weak correlation between QTd increase and arrhythmia occurrence was found. 68 The effects of volatile agents on ECG torsadogenic markers are presented in Table 1.…”
Section: Desfluranementioning
confidence: 96%
See 1 more Smart Citation
“…Desflurane was associated with persistent QTc prolongation (up to 30 min) in children, 54 and a high incidence (70%) of postoperative ventricular arrhythmias in adults. 68 A weak correlation between QTd increase and arrhythmia occurrence was found. 68 The effects of volatile agents on ECG torsadogenic markers are presented in Table 1.…”
Section: Desfluranementioning
confidence: 96%
“…68 A weak correlation between QTd increase and arrhythmia occurrence was found. 68 The effects of volatile agents on ECG torsadogenic markers are presented in Table 1. Data regarding halothane are not quite clear, while most studies indicate that isoflurane and desflurane prolong both QTc and QTd.…”
Section: Desfluranementioning
confidence: 96%
“…Even this issue is not entirely settled however, as some studies have shown that sevoflurane maintenance does not affect the QTc interval [30][31] . The literature is also inconsistent in regard to sevoflurane's effect on QTcd with some studies showing an increase [32][33][34] , and others showing a decrease 35 . In our study, in contrast to the increases in QTc interval, an overall neutral effect was observed for QTcd in both the groups compared to baseline.…”
Section: Discussionmentioning
confidence: 99%